Comparison of plant identifier application ability as a recommendation for biology learning - Wilsa, Asrizal; Nugroho, Sunyoto Eko; Prasetyo, Agung Tri (Biosfer: Jurnal Pendidikan Biologi, 2023)
This study aims to test the ability of the Plant Identifier application to identify plants as a recommendation for biology learning and practicum on plant identification and classification materials. The applications used in this research are Google Lens, Plant Net, Picture This, and Leaf Snap. Object samples include moss plants, ferns, dicot plants, and monocot plants. This study uses the VES (Visual Encounter Survey) method with an exploratory-descriptive approach. Application testing includes the speed of object detection, the accuracy of detecting objects based on shape and color, as well as the completeness of plant taxonomy information which includes division, class, order, family, genus, and species. The results of application testing show that: (1) the Google Lens and Picture This applications are superior in terms of speed in detecting objects, (2) Google Lens and Picture This are also superior in terms of accuracy in detecting objects based on shape and color, (3) the Picture This application is an application superior in completeness of taxonomic information. Based on these findings it can be concluded that the Picture This application is the most superior application and can be a recommendation for biology learning and practicum on plant identification and classification materials